124k views
5 votes
Factor the expression below x^2-12x+36

User Eliza
by
5.1k points

2 Answers

2 votes

Answer:

(X-6)(x-6)

Explanation:

User Nina Lisitsinskaya
by
5.8k points
3 votes
x^2-12x+36

Now, the constant term will be divided such that the factors sum or difference is equal to the middle term (coefficient of x)

36= 3*12
= 3*2*6
= 6*6

Hence, the two factors of 36 i.e. 6 and 6 gives the sum = 12.

Thus, we can write,

x^2-12x+36
= x^2-6x-6x+36
Taking common, we get,
= x(x-6)-6(x-6)
=(x-6)(x-6)

Thus, the two factors are (x-6) and (x-6)
User Beezz
by
5.5k points